3 Postprogression efficacy outcomes from the phase 3 ARIEL3 study of rucaparib in patients with platinum-sensitive recurrent ovarian carcinoma associated with either BRCA1 or BRCA2 mutations. (13th November 2020) - Weberpals, J; Oza, A; Lorusso, D; Scambia, G; Aghajanian, C; Oaknin, A; Dean, A; Colombo, N; Clamp, AR; Leary, A; Holloway, RW; Amenedo Gancedo, M; et al.
Abstract : Introduction: In ARIEL3 (NCT01968213 ), rucaparib maintenance for recurrent ovarian cancer (rOC) significantly improved investigator-assessed PFS and postprogression efficacy outcomes versus placebo regardless of biomarker status. PFS was also improved in patients with rOC associated with either BRCA1 or BRCA2 mutations (HR, 0.32 [95% CI, 0.19–0.53] and 0.12 [0.06–0.26], respectively). This exploratory analysis further examined the subgroup of patients with rOC associated with BRCA1 or BRCA2 mutations to assess the durability of the clinical benefit of rucaparib maintenance following disease progression. Methods: Patients were randomised 2:1 to oral rucaparib (600 mg twice daily) or placebo. Postprogression efficacy endpoints were assessed in patients with germline or somatic BRCA1 or BRCA2 mutations. Results: Investigator-assessed postprogression efficacy endpoints for patients with either BRCA1 or BRCA2 mutations are presented in the table 1 . There was a trend for better outcomes across all endpoints in patients with BRCA1 and BRCA2 mutations, with larger differences between the median values among patients with a BRCA2 mutation. The treatment-by-mutation group interaction test reached statistical significance for TFST and CFI. Among rucaparib-treated patients, the most common treatment-emergent adverse events (any grade) in the BRCA1 and BRCA2 subgroups were nausea (81.0% and 78.0%) and asthenia/fatigue (74.7% and 80.0%). Conclusions/Implications: All postprogression efficacy endpoints were longer with rucaparib maintenance than with placebo in both BRCA-mutant subgroups. Safety data for the two subgroups were similar and were consistent with the overall safety population.